Beta-Blocker Therapy Preserves Normal Splenic T-Lymphocyte Numbers Reduced in Proportion to Sepsis Severity in a Sepsis Model - Takeshi Suzuki; Kei Inoue; Toru Igarashi; Jungo Kato; Hiromasa Nagata; Takashige Yamada; Shizuka Minamishima; Hiroshi Morisaki (Critical Care Research and Practice)
Lymphocyte cell death contributes to sepsis-induced immunosuppression, leading to poor prognosis. This study examined whether sepsis severity and beta-blocker therapy could affect the degree of T-lymphocyte cell death in a mouse model of sepsis. In the first control study, 20 animals were allocated to 4 groups: control group with sham operation (group C, n = 5) and 3 groups with cecum ligation and puncture (CLP) performed at 3 different sites: proximal, middle, and distal cecum (groups CLP-P, CLP-M, and CLP-D, respectively; n = 5 in each group). Their spleens were resected under general anesthesia 24 hours after CLP, and the total number of normal splenic T lymphocytes per mouse and the percentage of apoptotic T lymphocytes were evaluated using flow cytometry. In the second experimental study, the effect of the beta-blocker esmolol was examined in CLP-P (group CLP-PE vs. CLP-P; n = 5 in each group). The total normal splenic T-lymphocyte numbers per mouse significantly decreased in proportion to CLP severity (group C, 18.6 × 106 (15 × 106–23.6 × 106); CLP-D, 9.2 × 106 (8.8 × 106–9.8 × 106); CLP-M, 6.7 × 106 (6.3 × 106–7.0 × 106); and CLP-P, 5.3 × 106 (5.1 × 106–6.8 × 106)). Beta-blocker therapy restored T-lymphocyte numbers (group CLP-PE vs. CLP-P; 6.94 ± 1.52 × 106 vs. 4.18 ± 1.71 × 106; p=0.027) without affecting apoptosis percentage. Beta-blocker therapy might improve sepsis-induced immunosuppression via normal splenic T-lymphocyte preservation.